Critical Influence of the Processing Route on the Mechanical Properties of Zirconia Composites with Graphene Nanoplatelets - Gallardo-López, Ángela (Materials (Basel), 2020)
Graphene-based nanostructures, used as potential reinforcement in ceramic composites, have a great tendency to agglomerate. This requires the use of homogenization techniques during the powder processing, posing the need to evaluate how these techniques affect the microstructure and the mechanical properties of the resulting composites. The influence of the processing route on the properties of 3YTZP (3 mol % yttria tetragonal zirconia polycrystals) ceramic composites with 10 vol % cost-effective GNP (graphene nanoplatelets) has been addressed. Four different powder processing routines combining ultrasonic powder agitation (UA) and planetary ball milling (PBM) in wet and dry media have been used and all the composites were densified by spark plasma sintering (SPS). The mechanical properties at room temperature in the macroscale have been assessed by Vickers indentations, four-point bending tests and the impulse-echo technique, while instrumented indentation was used to measure the hardness and Young’s modulus at the nanoscale. The application of dry-PBM enhances greatly the mechanical and electrical isotropy of the composites, slightly increases the hardness and lowers the elastic modulus, independently of the application of UA. The combination of UA and dry-PBM enhances the flexure strength by 50%, which is desirable for structural applications.